Analysis of Social and Economic Vulnerability to Landslides Disaster in Imogiri District, Bantul Regency - Fitri Febriani; Jumadi; Agus Sigit (Amcolabora, 2022)
Landslide, one of the natural disasters that often occur, especially in areas that have moderate to high slopes. Imogiri is a sub-district located in Bantul Regency. This sub-district has a percentage of relief of flat to wavy by 30% and relief of wavy to hilly by 70% with a predominantly clay texture. Therefore, Imogiri is included in an area that prones to landslides. In a history of disaster BPBD Bantul explained that there are several areas in Imogiri Subdistrict such as Village of Wukirsari, Sriharjo, Selopamioro, and Karangtengah which are in the red zone. According to the BPBD, in Bantul there were more than 2.000 people living in the red zone. Based on this statement, this study aims to analyze the areas in Imogiri Subdistrict which have low to high landslide hazard levels, as well as analyze the level of social and economic vulnerability of the people living in Imogiri Subdistrict, especially areas with potential landslides. The results obtained from this study in the form of landslide vulnerability maps, social vulnerability maps, and economic vulnerability maps. Based on the map, it can be analyzed that the Imogiri has a moderate level of landslide vulnerability, while the level of social and economic vulnerability in some areas shows a high level of vulnerability. This is influenced by population density, type of work, and its relationship with the level of landslide vulnerability in the areas.